Hubungan Tingkat Pengetahuan Ibu Balita Mengenai Pemberian Makanan Pendamping ASI (MP-ASI) Dengan Status Gizi Pada Balita Usia 6-24 Bulan Di Kelurahan Semanggi Kecamatan Pasar Kliwon Kota Surakarta - Widyawati, Wahyu, Dwi Sarbini, S.ST., M.Kes, Muwakhidah, SKM, M.Kes (2016)
Introduction: Complementary feeding is additional complementary foods given to infants aged 6-24 months to support growth and development. Given complementary food consider these things, the right given timeliness of administration, frequency, type, quantity of food, and how to make it. Results of preliminary studies conducted in the village of clover in December 2015, 45% of mothers and 25% less knowledgeable nutritional status of infants less. Objective: To determine the relationship between the mother's level of knowledge regarding the given of complementary feeding with nutritional status of infants aged 6-24 months. Research Method: This research is a cross-sectional study conducted in October 2015 until August 2016. The subjects were mothers and children aged 6-24 months from 101 people using multistage sampling. Questionnaire of MP-ASI knowledge and the research tool was dacin to the nearest 0,1 kg. Data analysis using Pearson Product Moment Correlation. Result: The level of mother knowledge about MP-ASI with a high score is 24,8%, with a middle score is 50,5%, and with a low score is 24,8%. Nutrition state (weight for age) good nutrition with amajority of 93,1%, children malnutrition by 1%, and stunting was 5,9%, and more nutrition 0%. There is a positive correlation between given MP-ASI with infant nutritional status aged 6-24 month is Kelurahan Semanggi Kecamatan Pasar Kliwon Kota Surakarta (p-value = 0,014). Conclusion: There is a positive correlation between given MP-ASI with infant nutritional status aged 6-24 month is Kelurahan Semanggi Kecamatan Pasar Kliwon Kota Surakarta Keywords: Knowledge Level Nutrition, Nutritional Status